PENGARUH PENINGKATAN PENGHASILAN TIDAK KENA PAJAK TERHADAP PENERIMAAN PAJAK STUDI PADA KPP YOGYAKARTA SATU - Nuritomo, Nuritomo (Jurnal Ilmiah Akuntansi dan Bisnis, 2011)
Non-taxable income (Penghasilan Tidak Kena Pajak/PTKP) is theminimum living cost to be able to live a decent life. Income tax is a subjectivetax, so that the imposition should consider personal factors which is realizedby granting concessions in the form of non-taxable income(PTKP).In 2004, the government issued Regulation of the Minister of FinanceNumber 564/KMK.03/2004 about Adjustment of taxable Income Amount,effective from year 2005 to replace Article 7 of Law No. 10 year 2000. TheAdjustment of PTKP in year 2004 was largest increase of 317%. PTKPincrease would affect tax revenues, particularly the income tax.This research was conducted to findout to what extent the effect ofPTKP increase on tax revenue, particularly to Article 21 of Income tax,individual income tax value added tax and luxury sales taxes. Sample takenis tax revenue of KPP Yogyakarta Satu serving Municipality of Yogyakartaand Bantul District. The data used is data in year 2001 until 2005.The results showed that the increase of PTKP gives effect to article 21income tax revenue, which decreased by 26.04%, while for individual incometaxes do not experience the effect of the increase which is marked by apermanent PTKP in a trend of increasing personal income tax amounting to36.94% . Value added tax and luxury sales tax in general do not experiencethe effect of increase PTKP.
Keywords: non-taxable income, personal income tax, VAT, sales tax, taxpayers.